2019
DOI: 10.1371/journal.pone.0220222
|View full text |Cite
|
Sign up to set email alerts
|

A fractionated analysis of hot and cool self-regulation in cigarette smokers from different socioeconomic backgrounds

Abstract: Smoking cigarettes and low socioeconomic status (SES) are both related to impaired cognition. However, it is unknown whether people of lower SES, who comprise most tobacco smokers worldwide, are more susceptible to cognitive impairment associated with smoking. In this non-randomized, cross-sectional study we investigated the effects of cigarette smoking, SES and their interaction on dissociable executive or “cool” and “hot” measures of behavioural self-regulation. Participants (n = 80) were selected among youn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 153 publications
(255 reference statements)
0
3
0
Order By: Relevance
“…Heavy current smokers indicated that they were more likely to decline a COVID-19 vaccine than current non-smokers. Smoking is linked to a raft of risk taking behaviours, impaired decision making and poor risk evaluations of the future consequences of actions [25] and these considerations could explain the much higher odds of refusing vaccines that we observed among heavy smokers. Mangtani and colleagues [26] recently showed that uptake of influenza vaccines differed by smoking status, whilst Jackson et al [27] highlighted that current smokers were more likely to be undecided or unwilling to receive a COVID-19 vaccine.…”
Section: Discussionmentioning
confidence: 89%
“…Heavy current smokers indicated that they were more likely to decline a COVID-19 vaccine than current non-smokers. Smoking is linked to a raft of risk taking behaviours, impaired decision making and poor risk evaluations of the future consequences of actions [25] and these considerations could explain the much higher odds of refusing vaccines that we observed among heavy smokers. Mangtani and colleagues [26] recently showed that uptake of influenza vaccines differed by smoking status, whilst Jackson et al [27] highlighted that current smokers were more likely to be undecided or unwilling to receive a COVID-19 vaccine.…”
Section: Discussionmentioning
confidence: 89%
“…Heavy current smokers indicated that they were more likely to decline a COVID-19 vaccine than current non-smokers. Smoking is linked to a raft of risk taking behaviors, impaired decision making and poor risk evaluations of the future consequences of actions ( 25 ) and these considerations could explain the much higher odds of refusing vaccines that we observed among heavy smokers. Mangtani et al ( 27 ) recently showed that uptake of influenza vaccines differed by smoking status, whilst Jackson et al ( 26 ) highlighted that current smokers were more likely to be undecided or unwilling to receive a COVID-19 vaccine.…”
Section: Discussionmentioning
confidence: 97%
“…Self-regulation is a complex and multifactorial concept [ 90 ] that acts at different executive functioning levels that represents the ability to voluntarily plan and modulate one’s behavior for an adaptive purpose [ 91 ]. Some authors consider the concept of behavioral self-regulation as synonymous with hot EFs [ 92 , 93 ], while others extend the concept, considering it as both hot and cold at the same time [ 94 ]. The Preschool Self-Regulation Assessment (PSRA) is used to evaluate hot and cold aspects where the focus is on the EF of delayed gratification [ 56 , 57 , 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%